2015
DOI: 10.1177/0269094215579014
|View full text |Cite
|
Sign up to set email alerts
|

Driving education for sustainable development potential within professional curricula: Built environment sustainability training and training development for professionals in Wales

Abstract: The Built Environment sector is responsible for 47% of all CO2 emissions, 90% of all surface mineral extraction and over 25% of all waste sent to landfill. In Wales, 30% of the carbon footprint comes from the built environment sector, a fact exacerbated also by having the highest proportion of pre-1919 building stock in the UK. None of these problems can be dealt with without having an appropriately skilled workforce, able to consider new technologies, applications and processes to deal with the problems of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Murray and Cotgrave (2007) explored the importance of sustainability literacy in constructing curriculum, while Robin et al (2019) assured the importance of sustainability literacy to help students understand sustainability and be more acknowledgeable about their roles. Hopkinson and Gwilliam (2015) indicated that sustainability literacy needs eligible learning methods such as blended approaches to enable students. UOS is the national coordinator for the UI Green Metric organization.…”
Section: Sustainability In University Of Sharjahmentioning
confidence: 99%
“…Murray and Cotgrave (2007) explored the importance of sustainability literacy in constructing curriculum, while Robin et al (2019) assured the importance of sustainability literacy to help students understand sustainability and be more acknowledgeable about their roles. Hopkinson and Gwilliam (2015) indicated that sustainability literacy needs eligible learning methods such as blended approaches to enable students. UOS is the national coordinator for the UI Green Metric organization.…”
Section: Sustainability In University Of Sharjahmentioning
confidence: 99%